Water quality of Kahta Stream (Adiyaman) discharging into Ataturk Dam Lake - Golbasi, Selami; Sen, Bulent (Ege Univ, Fac Fisheries, 2019)
In this study, it is aimed to determine the water quality of Kahta Stream which is poured into Ataturk Dam Lake by following some hydrological and physico-chemical characteristics between April 2012 and March 2013. For this purpose, monthly measurements were made at five stations from the source to the downstream and water samples were taken. During the monitoring period, water temperature 5.0-25.2 degrees C; electrical conductivity 216-359 pS/cm; total dissolved solids 147-244 mg/L; dissolved oxygen 8.67-13.36 mg/L and pH were measured in range of 7.08-8.76. Suspended solid 2-138 mg/L; turbidity 0.92-96.70 NTU; total alkalinity 102-200 mg/L; chloride 0.71-5.02 mg/L; ammonium nitrogen 0.007-0.400 mg/L; nitrite nitrogen 0.003-0.060 mg/L; nitrate nitrogen 0.12-1.19 mg/L; dissolved reactive phosphorus 0.007-0.033 mg/L; silica 5-23 mg/L; sulphate 8-33 mg/L and chemical oxygen demand were determined betwen 0.63-9.18 mg/L. Kahta Stream with slightly alkaline character, in terms of the parameters monitored, it is determined that the Surface Water Quality Regulation has the characteristics of Class I (high quality water) according to the Environmental Quality Standards. With this characteristic, it has been determined that Kahta Stream has a high potential to be used for drinking water supply, it can be used for re-use, trout farming, animal production and other farm needs. In addition, when the temporal relationship of variables was analyzed statistically, a significant difference was found among all variables except SiO2 (p <0.05). This result shows that the variables are affected by seasonal changes.
Keywords: Kahta Stream; Ataturk Dam Lake; water quality; limnology